267 ATTENUATION OF HEME INDUCTION FOLLOWING EXPOSURE TO TIN MESOPORPHYRIN IN MICE. (10th December 2015) - DeSandre, G. H.; Wong, R. J.; Morioka, I.; Vreman, H. J.; Stevenson, D. K.
Abstract : Heme oxygenase (HO) is the rate-limiting enzyme in the degradation of heme and produces equimolar amounts of carbon monoxide (CO), iron, and bilirubin. HO-1 can be induced by several conditions and compounds, including heme. Tin mesoporphyrin (SnMP), a competitive inhibitor of HO, is currently in clinical trials for use in the prevention of neonatal jaundice. Our objective was to determine the effect of SnMP on heme induction following heme exposure. In vivo heme degradation rates were measured by quantitating total body CO excretion (VeCO) in adult male mice (6-8 wk old) by gas chromatography (GC). After baseline VeCO were established, mice were administered 30-μM of hemin or SnMP or vehicle (VEH) by oral gavage (1st exposure). After 3 h of VeCO monitoring, mice were gavaged with 30-μM hemin or VEH (2nd exposure). VeCO levels were then followed until peak levels were reached. 24 h later, VeCO and liver, spleen, and intestine HO activity were quantitated by GC. All values are expressed as fold change (mean±SD) from control (*p≤0.05). (Table ) In the VEH-heme group, VeCO and liver HO activity significantly increased 2.8- and 1.8-fold following heme treatment, respectively. In the heme-heme group, VeCO increased 3.8- and 7.5-fold and following the 1 st and 2 nd heme exposure. Spleen and liver HO activities were 1.9- and 1.8-fold higher than controls, respectively. In mice pre-treated with SnMP, VeCO was 20% inhibited and did not increase following heme treatment. Spleen HO activity was inhibited by 40%. We conclude that successive exposures to heme does not alter VeCO rates, and that SnMP treatment attenuates heme-mediated increases in VeCO and HO activity. These findings suggest that SnMP is a potent inhibitor of HO with an effect lasting at least 24 h, which may be advantageous in the context of jaundice caused by an ongoing hemolytic process.